Understanding the Influence of Cybercrime Law Absence on Cyberbullying in Higher Institutions of Learning: A Case of the International University of Management - Iileka, Albertina; Kamati, Etuna; Nyalugwe, Symon Fumu (Journal of Information System and Informatics, 2023)
Cyberbullying is a serious problem that can have a significant negative impact on victims, including depression, anxiety, low self-esteem, and even suicidal thoughts. The absence of cybercrime laws can make it difficult to prosecute cyberbullying cases, which can contribute to the problem. The purpose of this study was to understand the influence of the absence of a cybercrime law on cyberbullying in higher institutions of learning. The study focused on the International University of Management (IUM) in Namibia. The study used mixed methods research design. Data was collected through an online questionnaire comprising both quantitative and qualitative questions. The link to the questionnaire was shared with students, as well as academic and administrative staff at IUM. The study found that the absence of a cybercrime law contributes to the problem of cyberbullying in IUM. The study also found that that there are a number of factors that contribute to cyberbullying in IUM, such as the use of social media, the anonymity that the internet provides, and the lack of awareness of cyberbullying among students and staff. The findings of the study have implications for policymakers, educators, and parents. Policymakers need to enact cybercrime laws to help prevent and prosecute cyberbullying cases. Educators need to educate students about cyberbullying and how to deal with it. Parents need to talk to their children about cyberbullying and monitor their online activity.